Setting up the right guardrails - SUNDER, Vijaya (Institutional Knowledge at Singapore Management University, 2024)
1. Emerging economies need public-private partnerships (PPPs) to deliver much-needed large-scale infrastructural projects. 2. An ‘orientation precedes strategy’ approach to partnerships generates wider societal acceptance and financial viability for stakeholders. 3. The stakeholder-orientation framework improves decision-making by promoting adaptability and inclusive engagement, as illustrated by the success of India’s Hyderabad Metro Rail Project.